PENGGUNAAN ALAT PERAGA ALAMIAH UNTUK MENINGKATKAN PEMAHAMAN SISWA TERHADAP MATERI BAGIAN TUMBUHAN DALAM PEMBELAJARAN IPA DI SD MUHAMMADIYAH 6 PALEMBANG - Fatimah, Siti (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This study aims to 1) increase the attention and involvement of fourth class students in science learning through the use of natural teaching aids; 2) Generating student motivation so that the teaching and learning process in science lessons will be more meaningful and passionate 3) Focus students' attention on the material being taught; 4) familiarize self-learning and find their own learning goals through observation of the surrounding environment. 5. Increase understanding of science subject matter. This research is a qualitative research. The research approach used is a case study. This study conducted a study by reviewing and describing the process of collecting and extracting data using the method of observation, interviews, and documentation. Data analysis techniques use qualitative data analysis techniques, using interactive analysis models. The results of this study are 1) for teachers that can develop their knowledge and skills and generate self-confidence so that they will always be passionate and eager to improve their learning continuously; 2) For students that can increase understanding in absorbing the material being studied so that the learning process and results will also increase too; 3) For schools, it is useful to assist schools in developing and creating quality education institutions that will be a model or model for schools, while teachers who are experienced professionals will be born and become the trust of parents and the government.